Absenteeism and Productivity Loss Due to Influenza or Influenza-like Illness in Adults in Europe and North America - David Fisman; Maarten Postma; Myron J. Levin; Joaquin Mould-Quevedo (Diseases)
Healthy working-age adults are susceptible to illness or caregiving requirements resulting from annual seasonal influenza, leading to considerable societal and economic impacts. The objective of this targeted narrative review is to understand the societal burden of influenza in terms of absenteeism and productivity loss, based on the current literature. This review includes 48 studies on the impact of influenza and influenza-like illness (ILI) and reports on the effect of influenza vaccination, age, disease severity, caring for others, comorbidities, and antiviral prophylaxis on absenteeism and productivity loss due to influenza/ILI, focusing on publications originating from Canada, Europe, and the United States. Influenza/ILI results in substantial work time and productivity loss among working adults and students in Canada, Europe, and the United States, particularly those who are unvaccinated, are <65 years of age, or who have severe disease. Considerable work time and productivity loss is attributable to illness and caregiver burden related to influenza. Further research is required on the impact of influenza on absenteeism and productivity loss in adults with comorbidities to support the development of effective employer policies for working adults with underlying health conditions.